Copolymerization of ethylene withdifferent α-olefins with poly(styrene-co- Divinylbenzene)-supported Cp[subscript 2]ZrCl[subscript 2]/MAO catalyst - Sompong Saetang (Chulalongkorn University, 2013)
Thesis (M.Eng.)--Chulalongkorn University, 2012